Recognizing faces under facial expression variations and partial occlusions - Faaya, Tiwuya H.; Toygar, Oensen (World Scientific And Engineering Acad And Soc, 2008)
Recognizing faces under facial expression variations and partial occlusions is presented in this paper. PCA- and LDA-based approaches with the combination of the preprocessing techniques of histogram equalization and mean-and-variance normalization are used in order to reduce the effect of partial occlusions, facial expressions and illumination variations. Various distance measures are applied for classification under different facial expression variations. To be consistent with the research of others, our work has been tested on the JAFFE database and its performance has been compared with traditional PCA and LDA methods.
7th WSEAS Int Conference on Signal Processing/2nd WSEAS Int Symposium on Wavelets Theory and Applicat in Appl Math, Signal Proc and Modern Sci -- MAY 27-30, 2008 -- Istanbul, TURKEY
Keywords: face recognition; facial expressions; face occlusion; PCA; LDA